Dynamics of ground beetle (Carabidae) populations at rock dumps in an open-pit coal mine: modeling the influence of environmental factors - Sergey L. Luzyanin; Anatoly A. Saveliev; Rifgat R. Shagidullin; Raisa A. Sukhodolskaya (Acta Biologica Sibirica, 2023)
Mineral mining's adverse environmental effects encompass pollution of air, surface, and ground waters, as well as soil disruption. Kuzbass (south of West Siberia, Russia) exemplifies this impact due to open-pit coal mining, leading to the emergence of man-made landscapes like dumps and quarries. Mining firms undertake reclamation efforts on post-technogenic zones. Evaluating dump restoration involves assessing vegetation and animal components, including soil invertebrates and ground beetles, which are sensitive bioindicators of environmental health. The ecological balance of any species hinges on various environmental factors, both biotic and abiotic. Determining the most influential factors for a species' ecological niche is challenging. This study is part of an extensive investigation into the succession of ground-dwelling arthropods across varying-aged coal mine rock dumps in Kuzbass. Pitfall traps were employed from 2013 to 2022, yielding over 47,000 ground beetle specimens. A unique statistical model, computed in R, gauged the impact of environmental factors on ground beetle abundance. Predictors encompassed ground level temperature, hydrothermal coefficient (HTC), soil pH, Soil Organic Carbon (SOC), Total N, vegetation cover, turf extent, and succession stage. All these factors significantly influenced beetle numbers. Probabilistic graphical models effectively elucidated key relationships between species groups and environmental variables. Monitoring ground beetle community succession in technogenic zones necessitates comprehensive consideration of intricate environmental interactions.